Fault detection in nonlinear systems via linear methods - Zhirabok, Alexey; Shumsky, Alexey; Solyanik, Sergey; Suvorov, Alexey (Zielona Góra: Uniwersytet Zielonogórski)
The problem of robust linear and nonlinear diagnostic observer design is considered. A method is suggested to construct the observers that are disturbance decoupled or have minimal sensitivity to the disturbances. The method is based on a logic-dynamic approach which allows us to consider systems with non-differentiable nonlinearities in the state equations by methods of linear algebra.
Keywords: nonlinear dynamic systems; diagnostic observers; robustness; non-differentiable nonlinearities; logic-dynamic approach